Social Marketing and Perceived Organizational Sustainability in Iraqi FMCG - Zaid Yaseen Saud (Indonesian Journal of Law and Economics Review, 2026)
General Background: Organizations are increasingly adopting sustainable business models to ensure long-term viability. Specific Background: Firms in the Iraqi Fast-Moving Consumer Goods (FMCG) sector face pressure to align corporate goals with social good through responsible communication. Knowledge Gap: Limited empirical data exists on how social marketing yields sustainable outcomes in emerging economies like Iraq. Aims: This study evaluates the relationship between social marketing practices and perceived organizational sustainability in the Iraqi FMCG industry. Results: Analysis of 384 consumers reveals a strong positive correlation, where ethical communication and social responsibility campaigns are the primary predictors of sustainability perceptions. Novelty: This research provides empirical evidence from a developing market, conceptualizing sustainability through consumer perception. Implications: FMCG managers should prioritize transparent and interactive marketing strategies to enhance organizational resilience and stakeholder trust. Highlights: Ethical communication and social responsibility campaigns are the primary drivers of perceived organizational sustainability in the Iraqi FMCG sector. Integrated marketing strategies significantly bolster consumer trust and support long-term economic stability. Digital awareness content is essential for enhancing organizational adaptability to changing market conditions. Keywords: Social Marketing, Perceived Organizational Sustainability, FMCG, Iraq, Ethical Communication